The broadcast century and beyond - Hilliard, Robert L., 1925- 4 0 16; 1945- , Keith, Michael C.; 5 (Amsterdam : Elsevier/Focal Press, 2010)
A history of broadcasting in the United States, arranged year-by-year, covering the technological innovations that made radio and television broadcasting possible and later improved it, as well as the companies and individuals who have played a pivotal role in the dynamic industry.
Includes bibliographical references (p. 353-357) and index.
Keywords: 2 -- 0; 6; History. -- Broadcasting -- United States -- 20; 20; 2